Synthesis and properties of 2′-O, 4′-C-spirocyclopropylene bridged nucleic acid (scpBNA), an analogue of 2′, 4′-BNA/LNA bearing a cyclopropane ring1. Issue 47 (14th June 2015) - Yamaguchi, Takao; Horiba, Masahiko; Obika, Satoshi
<x xml:space="preserve">Abstract</x> The scpBNA-modified oligonucleotides exhibit excellent duplex-forming ability toward the complementary ssRNA, and dramatically increased resistance to nuclease activity compared to their 2′, 4′-BNA/LNA-modified counterparts.